Tropical Forests Of Oceania. Anthropological Perspectives - A. Bell, Joshua (ANU Press, 2015)
The tropical forests of Oceania are an enduring source of concern for indigenous communities, for the migrants who move to them, for the states that encompass them within their borders, for the multilateral institutions and aid agencies, and for the non-governmental organisations that focus on their conservation. Grounded in the perspective of political ecology, contributors to this volume approach forests as socially alive spaces produced by a confluence of local histories and global circulations. In doing so, they collectively explore the multiple ways in which these forests come into view and therefore into being. Exploring the local dynamics within and around these forests provides an insight into regional issues that have global resonance. Intertwined as they are with cosmological beliefs and livelihoods, as sites of biodiversity and Western desire, these forests have been and are still being transformed by the interaction of foreign and local entities. Focusing on case studies from Papua New Guinea, the Solomon Islands and the Gambier Islands, this volume brings new perspectives on how Pacific Islanders continue to creatively engage with the various processes at play in and around their forests.